Celluloid skyline New York and the movies - Sanders, James 1955- (Alfred A. Knopf, 2003)
Explores how movies have shaped, influenced, mythologized, and invented New York City in such films as "42nd Street," "Rear Window," "Taxi Driver," "Annie Hall," and "Ghostbusters," and reveals how the real-life New York City has been transformed by Hollywood.